The level of sialic acids and imidazole compounds in the saliva of patients with lung cancer of different histological types - L. V. Belskaya; V. K. Kosenok (Сибирский онкологический журнал)
In recent years, the possibility of using known and new tumor markers in primary and differential diagnosis of lung cancer has been actively studied.The purpose of the study was to study the level of sialic acids, the total content of imidazole compounds and seromucoids in the saliva of patients with lung cancer, depending on the histological type of tumor.Material and Methods. Total of 478 people took part in in the case-control study. They were divided into 3 groups: the main group (lung cancer, n=218), the comparison group (nonmalignant lung pathologies, n=60) and the control group (conditionally healthy, n=200).Results. Patients with non-malignant lung pathologies exhibited increased levels of imidazole compounds and seromucoids and decreased levels of sialic acids. A statistically significant decrease in the level of sialic acids was observed in patients with non-small cell lung cancer. The concentration of imidazole compounds was significantly higher in all study groups, except for carcinoid tumors. The nature of the changes in the studied parameters were ambiguous and depended on both the histological type of the tumor and the stage of the disease, including the presence / absence of distant and regional metastasis.